Design and Biological Evaluation of Delivery Systems Containing Bisphosphonates - Blessing Aderibigbe; Isiaka Aderibigbe; Patricia Popoola (Pharmaceutics, 2016)
Bisphosphonates have found application in the treatment of reoccurrence of bone diseases, breast cancer, etc. They have also been found to exhibit antimicrobial, anticancer and antimalarial activities. However, they suffer from pharmacological deficiencies such as toxicity, poor bioavailability and low intestinal adsorption. These shortcomings have resulted in several researchers developing delivery systems that can enhance their overall therapeutic effectiveness. This review provides a detailed overview of the published studies on delivery systems designed for the delivery of bisphosphonates and the corresponding in vitro/in vivo results.